ANALISIS KESULITAN BELAJAR MAHASISWA PADA MATA KULIAH ALJABAR LINEAR (STUDI KASUS PADA MAHASISWA MANAJEMEN INFORMATIKA AKADEMI MANAJEMEN BELITUNG) - Djunaedi Djafar; Eka Indah Wahyuni; Leni Reziyustikha (Jurnal Prinsip Pendidikan Matematika, 2019)
The purpose of this study is to determine the difficulties of students in linear algebra subject. The subject of linear algebra is one of the compulsory subjects in the Informatics Management Study Program. From the last 3 years, in linear algebra subject, students who get below average scores are always there. Difficulties in linear algebra subject need to be analyzed so that it can be known the cause of the difficulties. The study was conducted on informatics management students in 2019/2020. From this study, the causes of difficulties in algebra are 1) the lack of skilled students in integer operations, 2) students didn’t thorough, 3) student logic ability is still lacking to do Elementary Row Operations, 4) students doubt in solving problems.